The effect of Integrated Amrita Meditation (IAM) Technique on Glycemic Control in Type 2 Diabetes (International Journal of Physiology, 2019)
ObjectiveTo determine the effect of Integrated Amrita Meditation (IAM) technique on glycemic control and short term stress response in type 2 diabetic subjectsStudy DesignThirty eligible type 2 diabetic patients were screened and informed about the study. After the initial drop out, ten diabetic subjects between age group of 30–60 years who agreed to participate were randomized to IAM and control groupInterventionParticipants in the IAM group practiced the meditation for 23 min/day for duration of three months and the control group participants continued with their daily routines without practicing any form of yoga and/or meditationResultsWithin group analysis of IAM group showed a statistically significant decrease in weight, BMI, heart rate, systolic BP, fasting blood glucose, HbA1c, cortisol and perceived stress score. Between group analysis showed significant differences in the percentage change for Weight, BMI, Heart rate, Systolic BP, Fasting Blood Glucose, HbA1c, Insulin resistance, Cortisol and PSS from baseline to three months.ConclusionOur study shows the efficacy of the technique in bringing about a better glycemic control and psychological stress reduction in type 2 diabetic subjects